Valuing a risky prospect less than its worst outcome: uncertainty effect or task ambiguity? - Andreas Ortmann; Alexandra Prokosheva; Ondřej Rydval; Ralph Hertwig (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2007)
Gneezy, List and Wu [Q. J. Econ. 121 (2006) 1283-1309] document that lotteries are often valued less than the lotteries worst outcomes. We show how to undo this result.
Keywords: C81; C91; C93; D83; 330; Risky choice; framing; experiments; task ambiguity; subject confusion; Entscheidung bei Risiko; Framing; Test